Conservation Traps and Long‐Term Species Persistence in Human‐Dominated Systems. Issue 6 (23rd February 2015) - Cardador, Laura; Brotons, Lluís; Mougeot, François; Giralt, David; Bota, Gerard; Pomarol, Manel; Arroyo, Beatriz
Abstract: Major conservation efforts in human‐dominated systems, such as farmland, have focused on the establishment of subsidies and compensation promoting low‐impact management practices to reverse the impacts of conservation threats in the short term (reactive approaches). In this study, we discuss how a different way of framing conservation policy (proactive approaches) could lead to fundamentally different long‐term conservation outcomes. We define proactive approaches as those not necessarily including measures directly addressing the threats affecting biodiversity, but promoting transitions from current scenarios in which species are threatened to new states in which the threat is no longer present. We illustrate reactive and proactive approaches using as a case study two contrasting conservation frameworks for a vulnerable farmland bird, the Montagu's harrier ( Circus pygargus ) in northeastern Spain. This example shows that reactive approaches can lead to "conservation traps, " which we defined as situations where the application of biologically focused actions in response to conservation problems results in an unsustainable need to perpetuate the implementation of those actions. Our aim is to offer a fresh perspective on biodiversity conservation in human‐dominated systems and to stimulate alternative, more holistic approaches in conservation promoting transitions to new states not requiring long‐term active and costly conservation action.